Presagios de independencia política en el Seminario y Colegio de San Nicolás Obispo en Valladolid - María del Carmen Rovira Gaspar (Theoría Revista del Colegio de Filosofía, 2013)
In this paper I analyze and study the presages of the Independence or, like I like to say, the academic and intelectual revolution that happened in the Seminar and College of San Nicolas Obispo as an antecedent of the political Independence.